Pengaruh Direct Marketing terhadap Keputusan Pembelian pada Live Streaming Tiktok dengan Kepercayaan sebagai Variabel Moderasi dalam Perspektif Bisnis Islam : Study pada Generasi Z Pengguna Aplikasi Tiktok di Kota Bandar Lampung - Fatih Fuadi; Adib Fachri; Feby Amelia (Journal of Islamic Economics and Finance, 2024)
The development of the times is constantly changing, marked by the existence of various applications that have online promotion and sales features. competition in online sales is getting tighter, making online business people look for the right strategy to market their products, such as in the TikTok strategy application so that consumers are easy to make a purchasing decision, namely with its latest feature, namely live streaming, which can be seen from direct marketing and trust. The purpose of this study was to determine the effect of direct marketing on purchasing decisions with trust as a moderating variable in an Islamic business perspective. This research uses quantitative methods. Data collection techniques in literature review, questionnaires and Likert scales. The population used in this study is generation z in Bandar Lampung City. Sampling in this study using purposive sampling technique. The number of samples used, determined by the formula according to Widianto, amounted to 97 respondents. The data analysis method uses Partial Last Scructural Equation Modeling (PLS-SEM) and data processing using smartPLS software. The results of this study indicate that there is a positive and significant influence between direct marketing on purchasing decisions. And trust does not moderate the relationship between direct marketing and purchasing decisions. In the perspective of Islamic business direct marketing on purchasing decisions on live streaming tiktok has implemented the principles of Islamic business ethics, including unity, balance, free will, responsibility, and benevolence so that it is something that Muslim business people need to pay attention to.